In Situ Electrochemical Monitoring of Caged Compound Photochemistry: An Internal Actinometer for Substrate Release - Jarosova, Romana; Kaplan, Sam V; Field, Thomas M; Givens, Richard S; Senadheera, Sanjeewa N; Johnson, Michael A (Analytical chemistry, 2021)
Caged compounds are molecules that release a protective substrate to free a biologically active substrate upon treatment with light of sufficient energy and duration. A notable limitation of this approach is difficulty in determining the degree of photoactivation in tissues or opaque solutions because light reaching the desired location is obstructed. Here, we have addressed this issue by developing an in situ electrochemical method in which the amount of caged molecule photorelease is determined by fast-scan cyclic voltammetry (FSCV) at carbon-fiber microelectrodes. Using p-hydroxyphenyl glutamate (pHP-Glu) as our model system, we generated a linear calibration curve for oxidation of 4-hydroxyphenylacetic acid (4HPAA), the group from which the glutamate molecule leaves, up to a concentration of 1000 μM. Moreover, we are able to correct for the presence of residual pHP-Glu in solution as well as the light artifact that is produced. A corrected calibration curve was constructed by photoactivation of pHP-Glu in a 3 μL photoreaction vessel and subsequent analysis by high-performance liquid chromatography. This approach has yielded a linear relationship between 4HPAA concentration and oxidation current, allowing the determination of released glutamate independent of the amount of light reaching the chromophore. Moreover, we have successfully validated the newly developed method by in situ measurement in a whole, intact zebrafish brain. This work demonstrates for the first time the in situ electrochemical monitoring of caged compound photochemistry in brain tissue with FSCV, thus facilitating analyses of neuronal function.
Keywords: elektrochemické techniky; Electrochemical Techniques; karbonové vlákno; dánio pruhované; Animals; Carbon Fiber; fotochemie; Microelectrodes; Zebrafish; mikroelektrody; zvířata; Photochemistry